FISHERY AND BIOLOGY OF METAPENAEUS MONOCEROS (FABRICIUS) FROM THE GODAVARI ESTUARINE SYSTEM - Subramanyam, M (Indian Journal of Fisheries, 2011)
Metapenaeus monoceros (Fabricius) is one of the important commercial prawns and comprises about 42% in tiie total prawn landing in the Gautami estuary. It is abundant in the lower reaches of the estuaries, particularly in the mangrove swamps and backwaters. The main fishing season extends from October to January/February and the dominant sizes in the commercial catches range between 26 mm and 65 mm. Drag nets and stake nets are the main gear employed in the capture fishery. Under laboratory conditions the average growth rate was about 13 mm/month, while the estimated growth from size frequency distributions ranged between 5 mm and 15 mm/month. The size of the prawn leavinj the estuary was 45-50 mm- Laboratory experiments showed that the prawns were active at night and bur.owed into the substratum during the day- The post-larvae entered the estuary in large numbers at night almost throughout the year. The overall sex ratio of the prawns was more or less unity. Plant matter, organic detritus, small crustaceans and foraminiferan shells formed the main diet of the prawn.